Analisis Perubahan Ketentuan Transfer Pricing dalam Peraturan Menteri Keuangan No. 172 Tahun 2023 dengan Peraturan yang Digantikannya - Firgia Ekklesia Heilbron (CV. Ulil Albab Corp, 2025)
Minister of Finance Regulation (PMK) Number 172 of 2023 introduces significant reforms in tax policy, focusing on administrative simplification, enhanced transparency, and harmonization with international standards. This regulation replaces PMK 213 of 2016 and other regulations, which previously governed the arm's length principle in related-party transactions. PMK 172 expands the scope of regulation, strengthens the authority of tax officials, and provides more detailed documentation guidelines to support transfer pricing supervision. Furthermore, this regulation aligns tax policies with strategic needs to encourage investment and improve Indonesia's competitiveness. The reform aims to provide legal certainty, simplify access to incentives for eligible taxpayers, and promote priority sectors such as technology, manufacturing, and renewable energy. PMK 172 not only aligns domestic policies with international practices but also strengthens a fair and sustainable tax system